Die jungpleistozäne Vergletscherung des Qinling Shan (Provinz Shaanxi).: Ein Beitrag zur Vergletscherungsproblematik ostchinesischer Gebirge - Rost, Karl Tillmann (ERDKUNDE, 1993)
Since the early investigations of LEE and v. WISSMANN, the question of Pleistocene glaciations in the mountains of East-China is strongly discussed. The central Qinling Shan (33°58 'N/107°45 'E) plays a key role by reconstructing the Pleistocene glaciations in the mountains of East-China. Recent geomorphological investigations prove the existence of late- Pleistocene glaciations in the Taibai Shan massif and lead to the hypothesis of a temporarily existing, small icecap with five minor outlet-glaciers around Ba Xian Tai (3767 m) and West-Po Ma Liang ridge (3450-3715 m). In the valleys around Ba Xian Tai several moraines exist above 2850 m a.s.l. Besides younger terminal moraines, representing stages of glacier retreat, the moraines were accumulated before 18,000 years B.P., as proved by two TL-datings. The lowest late-Pleistocene altitude of the glacier-snowline at 3250-3300 m a.s.l. is deduced from the lowest moraines. The resulting snowline depression was about 1000-1300 m, compared to the supposed present position. Remnants of older Pleistocene glaciations in other areas of Qinling Shan below 2600 m have not been observed. The morphological results from central Qinling Shan are compared with geomorphological findings in the neighbouring ranges Helan Shan (Inner Mongolia/Ningxia) and Minshan (Sichuan). The altitude of the late-Pleistocene snowline has increased from 3000-3100 m in the Helan Shan to 4000 m in the Minshan. Reports of Quaternary glaciations in mountain ranges below 2500 m a.s.l. in northeast China remain rather questionable.